The Effect of Social Media Marketing Effort on Customer Response Through Brand Equity in Starbucks Store - Yessica Ayu Febryanta Ginting (International Journal of Social Service and Research, 2022)
This study aims to analyze the effect of Social Media Marketing Efforts on Customer Response, the Effect of Social Media Marketing Efforts on Brand Equity, the Effect of Brand Equity on Customer Response, and the Effect of Social Media Marketing Efforts on Customer Response through Brand Equity in Starbucks Store. Furthermore, this study also aims to analyze the most effective policies that can be implemented by Starbucks management in an effort to implement Social Media Marketing Efforts and increase the level of Brand Equity products and Customer Response at the Starbucks Store. This research was conducted in three Starbucks District 33 Medan store (Hermes, Focal Point and Manhattan). The number of samples of this study amounted to 185 people. The analytical method in this study uses the Structured Equation Model (SEM) with the Smart PLS 3.0 Program. The results of this study found that Social Media Marketing Efforts had a positive and significant effect on Customer Response, Social Media Marketing Efforts had a positive and significant effect on Brand Equity, Brand Equity had a positive and significant effect on Customer Response, and Brand Equity was able to mediate the influence of Social Media Marketing Efforts towards Customer Response. Starbucks management can apply strategies such as: increased brand awareness, import reputation, increased relationship, brand development, and increased purchase intention.